2019
DOI: 10.1051/epjconf/201920508011
|View full text |Cite
|
Sign up to set email alerts
|

Antiresonant-like behavior in carrier-envelope-phase-sensitive sub-optical-cycle photoemission from plasmonic nanoantennas

Abstract: Optical-field-driven photoemission occurs when the electric field of an optical pulse bends the potential barrier of a material surface such that electron tunneling occurs before the field reverses polarity. At the surface of nanoscale structures, such as ultra-sharp nanoscale tips or metallic nanoantennas, the electric fields of ultrafast optical pulses are strongly enhanced. These enhanced fields can drive optical-field photoemission (i.e. optical-tunneling) and thereby generate and control electrical curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Using plasmonic nanoantennas, the incident optical fields can be enhanced across a broad bandwidth near the structure's plasmonic resonance, allowing for optical-field photoemission to be achieved using much lower incident optical pulse energies. Recent studies have demonstrated that by driving such nanoantennas with few-cycle optical pulses, an appreciable CEP-sensitive photocurrent can be generated using only picojoules of energy at repetition rates approaching 100 MHz [6,7,8,9]. With proper engineering, such nanoantenna-enhanced photodetectors could lead to compact and integratable CEP-sensitive detectors that provide shot-to-shot CEP stabilization and control for compact frequency combs and few-cycle optical sources [10].…”
Section: Introductionmentioning
confidence: 99%
“…Using plasmonic nanoantennas, the incident optical fields can be enhanced across a broad bandwidth near the structure's plasmonic resonance, allowing for optical-field photoemission to be achieved using much lower incident optical pulse energies. Recent studies have demonstrated that by driving such nanoantennas with few-cycle optical pulses, an appreciable CEP-sensitive photocurrent can be generated using only picojoules of energy at repetition rates approaching 100 MHz [6,7,8,9]. With proper engineering, such nanoantenna-enhanced photodetectors could lead to compact and integratable CEP-sensitive detectors that provide shot-to-shot CEP stabilization and control for compact frequency combs and few-cycle optical sources [10].…”
Section: Introductionmentioning
confidence: 99%